Traditional Games and Sports of the Women in the Kabylie - Nefil, Iman; Laaouad-dodoo, Soraya; Bordes, Pascal; Torki, Ahmed (Frontiers in Psychology, 2021)
With regard to the issue of the differences of the sexes, our study focuses on traditional games in Kabylie, taken and defined as part of the field of motor praxiology. A discipline inspired by the work of Pierre Parlebas. We will attempt through a field survey, to identify and interpret the meaning and distribution of the traditional games played by the women of Kabylie. From this perspective, the analysis of the internal logics of the practices are related to the system of interactions between players and their environment. This reveals valuable information on the structures underlying traditional games, and their ethno-motor characteristics as well as the world of ethnology of this vast mountainous region of Kabylie. By analyzing 92 traditional games played in the region of Kabylie allowed us to highlight on the one hand the cultural specificity, and on the other the richness of the socio-cultural aspects of this region. By examining how a game constitutes a cultural identity element of a geographical space, we explain the meaning of sport culture and identity of the Kabylie, by focusing particularly on the place of women and the indicators that reveal the relationships between men and women and distinguish the distribution of female and male roles. This also allows an understanding of the nature of traditional sports and their differentiation in terms of socialization between boys and girls.